Low molecular weight dextran provides similar optical coherence tomography coronary imaging compared to radiographic contrast media. Issue 5 (1st August 2013) - Frick, Kyle; Michael, Tesfaldet T.; Alomar, Mohammed; Mohammed, Atif; Rangan, Bavana V.; Abdullah, Shuaib; Grodin, Jerrold; Hastings, Jeffrey L.; Banerjee, Subhash; Brilakis, Emmanouil S.
<x xml:space="preserve">Abstract</x> Background Optical coherence tomography (OCT) coronary imaging requires displacement of red blood cells from the vessel lumen. This is usually accomplished using radiographic contrast. Low molecular weight dextran has low cost and is safe in low volumes. In the present study, we compared dextran with contrast for coronary OCT imaging. Methods Fifty‐one vessels in 26 patients were sequentially imaged using manual injection of radiographic contrast (iodixanol) and dextran. OCT images were analyzed at 1 mm intervals to determine the image clarity (defined as a visible lumen border > 270°) and to measure the lumen area and lumen diameter. To correct for the refractive index of dextran, the dextran area measurements were multiplied by 1.117 and the dextran length measurements were multiplied by 1.057. Results A total of 3, 418 cross‐sections (1, 709 with contrast and 1, 709 with dextran) were analyzed. There were no complications related to OCT imaging or to contrast or dextran administration. Clear image segments were observed in 97.0% vs. 96.7% of the cross‐sections obtained with contrast and dextran, respectively (P = 0.45). The mean lumen areas were also similar: 6.69 ± 1.95 mm2 with iodixanol vs. 7.06 ± 2.06 mm2 with dextran (correlation coefficient 0.984). Conclusions The image quality and measurements during OCT image acquisition are similar for dextran and contrast. Dextran could be used instead of contrast for OCT imaging, especially in patients in whom contrast load minimization is desired. © 2013 Wiley Periodicals, Inc.